The Effect of Work Experience, Compliance Pressure, Self-Efficacy and Gender on Audit Judgement - Luthfi’ah Rizki Hastuti; Samsul Rosadi (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The goal of this research is to analyze the impact of work experience, compliance pressure, self-efficacy, and gender on audit judgment among auditors. In an increasingly complex auditing environment, understanding the factors that shape auditors’ professional judgments is crucial. The study utilized a quantitative method, gathering primary data from surveys given to auditors employed at Public Accounting Firms located in Surakarta and Semarang areas. In this study, 65 participants were chosen using purposive sampling, meeting certain predetermined requirements. The research instrument was measured using a Likert scale, and the data were analyzed using multiple linear regression with the aid of SPSS software. The findings indicate that work experience, self-efficacy, and gender have a significant positive effect on audit judgment, suggesting that these factors contribute to more confident and informed decision-making in the auditing process. In contrast, compliance pressure negatively affects audit judgment, highlighting the need for firms to manage organizational pressures to maintain audit quality.